"Epistemologias do Ensino de Cartografia Escolar no Brasil: um Estudo sobre as Bases Teóricas e Metodológicas - CARLOS SIQUEIRA PEIXOTO (2025)
The relationship between Geography and School Cartography is highly relevant in the current educational context. The map plays a fundamental role in Geography teaching, as it is a powerful tool that enables the visual and accessible representation and understanding of geographic space. This study is grounded in the premise that two main theoretical-epistemological frameworks support research in School Cartography: Jean Piaget’s Genetic Epistemology and Lev Vygotsky’s Socio-Historical Theory. The objective of this research was to identify the main epistemological approaches underpinning research and teaching practices in School Cartography in Brazil between 2001 and 2023. The study adopts the Hypothetical-Deductive Method (HDM), characterized by the formulation of hypotheses that can be confirmed or refuted. The theoretical framework discusses epistemology and Geography, including recent developments in the field, and examines the role of official documents issued by Brazil’s Ministry of Education (MEC), which have been essential in shaping the national Geography curriculum in recent decades. The study also details the research methodology, including a discussion on the concepts and applications related to metaresearch, content analysis, and the use of Iramuteq® software. The research employs a qualitative-quantitative approach and is structured as a metaresearch study, with a focus on content analysis using Iramuteq®. Dissertations and theses were sourced from the Brazilian Digital Library of Theses and Dissertations (BDTD) and the CAPES Theses and Dissertations Catalog. The selected documents were classified into four categories based on thematic lines established by the Cartography Colloquia. The findings indicate an overall increase in academic production over the selected years, with a significant decline between 2020 and 2021, followed by a steady rise in 2022 and 2023. The textual corpus was processed using Iramuteq®, enabling statistical analyses through Descending Hierarchical Classification (DHC), which identified six thematic categories across the analyzed studies: Research Methodology, School Context and Educational Levels, Teacher Training and Practice, Cognitive Development and Geographic Thinking, Spatial Reading and Representation, and Technologies and Multimodality. The similarity analysis revealed the study’s key finding: the existence of eight epistemological approaches—Genetic Epistemology, Socio-Historical Theory, Phenomenology, Historical-Dialectical Materialism, Multiple Intelligences Theory, Rhizome Theory, Philosophy of Difference, and Materiality and Communication. While Piaget’s and Vygotsky’s theories remain predominant in School Cartography in Brazil from 2001 to 2023, other theoretical-epistemological perspectives have also supported teaching and research in this field. The content analysis enabled by Iramuteq® made it possible to identify, categorize, and understand the main epistemological trends in academic research on School Cartography, as the methodological design allowed for a robust documentary analysis and the identification of the leading theoretical-epistemological currents.